2010
DOI: 10.1371/journal.ppat.1001205
|View full text |Cite
|
Sign up to set email alerts
|

Tick Histamine Release Factor Is Critical for Ixodes scapularis Engorgement and Transmission of the Lyme Disease Agent

Abstract: Ticks are distributed worldwide and affect human and animal health by transmitting diverse infectious agents. Effective vaccines against most tick-borne pathogens are not currently available. In this study, we characterized a tick histamine release factor (tHRF) from Ixodes scapularis and addressed the vaccine potential of this antigen in the context of tick engorgement and B. burgdorferi transmission. Results from western blotting and quantitative Reverse Transcription-PCR showed that tHRF is secreted in tick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
146
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(155 citation statements)
references
References 36 publications
2
146
1
6
Order By: Relevance
“…The specificity of Abs to both 24 h and 48 h TSPs as well as the reactivity of mono-specific Abs to r Aam AV422 on western blots of r Aam AV422, tick saliva, haemolymph and dissected tick organs led us to conclude that this protein was ubiquitously expressed and injected into the host within 24 h of tick feeding. In the literature two other cross-tick species conserved TSPs, tick calreticulin (Sanders et al, 1998, 1999; Ferreira et al, 2002; Xu et al, 2004, 2005; Alarcon-Chaidez et al, 2006; Gao et al, 2008; Kaewhom et al, 2008; Parizi et al, 2009) and histamine release factor (Mulenga et al, 2003a Mulenga and Azad, 2005; Dai et al, 2010) have been described. A common feature between tick calreticulin and histamine release factor is that they both have homologs in vertebrates (Mulenga et al, 2003b, Mulenga and Azad, 2005; Coe and Michalak, 2009; Martins et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of Abs to both 24 h and 48 h TSPs as well as the reactivity of mono-specific Abs to r Aam AV422 on western blots of r Aam AV422, tick saliva, haemolymph and dissected tick organs led us to conclude that this protein was ubiquitously expressed and injected into the host within 24 h of tick feeding. In the literature two other cross-tick species conserved TSPs, tick calreticulin (Sanders et al, 1998, 1999; Ferreira et al, 2002; Xu et al, 2004, 2005; Alarcon-Chaidez et al, 2006; Gao et al, 2008; Kaewhom et al, 2008; Parizi et al, 2009) and histamine release factor (Mulenga et al, 2003a Mulenga and Azad, 2005; Dai et al, 2010) have been described. A common feature between tick calreticulin and histamine release factor is that they both have homologs in vertebrates (Mulenga et al, 2003b, Mulenga and Azad, 2005; Coe and Michalak, 2009; Martins et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…F2 crossbreeds of these two cattle were resistant to R. microplus infestation, with feeding with R. microplus larvae inducing significant increases in dermal mast cell numbers. Mast cells are major producers of the inflammatory mediator histamine, and ticks can affect histamine actions by either binding histamine via histamine-binding lipocalins [93, 94] or by promoting its secretion via histamine release factor [95], further evidence of the ambiguous role for mast cells in tick feeding responses. One explanation for histamine binding followed by its release can be explained by the need to suppress inflammatory responses at the early stage of feeding, followed by an increased need for vascular permeability during the rapid engorgement phase of tick feeding.…”
Section: Mast Cells and Tick Salivamentioning
confidence: 99%
“…After migration to the site of injury, basophils degranulate and release mediators such as histamine to reject ticks in a host reaction known as cutaneous basophil hypersensitivity [103]. Similar to mast cells, histamine release from basophils can be mediated by tick histamine release factor binding [95]. Several studies have confirmed the role of basophils in acquired immunity against ticks in mice [102, 104, 105].…”
Section: Basophils and Tick Salivamentioning
confidence: 99%
“…These include salivary proteins such as tick histamine release factor [147], Salp15 [52], and the lectin complement pathway inhibitor (TSLPI) [145]; the latter two provide protection for B. burgdorferi against components of the host immune system. Salivary proteins Salp14 [49], Salp16 [48], and Salp25D [44] have been examined for their function in acquiring A. phagocytophilum or B. burgdorferi through RNAi.…”
Section: Understanding Tick-pathogen Interaction Through Rnaimentioning
confidence: 99%